Scientometric analysis of global cyber security research output based on Web of Science - Shettar, Iranna; Hadagali, Gururaj S.; Kaddipujar, Manjunath; Bulla, Shivanand D.; Agadi, Kotrayya; Ganjihal, Gireesh A.; Hiremath, Rudramuni; Dundannanavar, Akshaykumar; Babu, B. Ramesh (Iberoamerican Journal of Science Measurement and Communication, 2024)
Objective. This study aims to analyze global cyber security research using various scientometric indicators for 25 years, from 1999 to 2023. Design/Methodology/Approach. The study used the Web of Science international citation database to retrieve a total of 5,640 records. The records were extracted in the CSV file format and further analyzed using an MS-Excel spreadsheet, VosViewer, and Biblioshiny software. Findings. The findings revealed that a 300% annual growth rate was recorded for the publications in 2002. The USA emerged as the top contributor (31.15%) among the countries. The authors affiliated with the State University System of Florida have more publications (107 contributions). Authors Lingfeng Wang of the University of Wisconsin-Milwaukee and Kim-Kwang Raymond Choo of the University of Texas at San Antonio have contributed the equal and highest number of (21) papers. Originality/Value. Cyber security research helps to guardian the individual or nation’s digital sovereignty, protecting it against sophisticated cyber threats and potential attacks. The discipline has become the subject of global research. This study helps cyber security experts, software or web developers, and researchers identify the primary research evidence and its impact on the research community and policymakers for evidence-based policymaking to combat invisible global threats.